Energy security assessment in rural communities in Brazil: A contribution to public policies - Wesly Jean; Marcel Bursztyn; Elton S. Oliveira; Júlia Lopes; Guadalupe Sátiro; Saulo Rodrigues Filho; Diego Lindoso; Juliana Dalboni Rocha; Nelson Bernal; Daniela Nogueira (Energy Nexus)
Energy security refers to the continuous and reliable access to energy sources at an affordable cost. In rural areas, particularly in Brazil's semi-arid regions, this security is essential for the survival and development of communities. This research analyzes energy security levels and their interfaces with water, food and socioecological security. The nexus+ approach has been used as a theoretical framework. This case study focuses on a settlement of small-scale family farmers in the semiarid region of northeastern Brazil. An extensive literature review on energy security and energy transition was carried out. Four pilot agri-villages were considered. The methodology of this study employs a multi-criteria analysis using the analytical hierarchy process (AHP). This approach supports decision-making across various criteria, both quantitative and qualitative. Additionally, QGIS software was utilized to create thematic maps by categorizing defined classes and using the raster calculator function. To determine the degree of energy security in each agri-village, five classes were defined. Among the scenarios analyzed, the main results indicate that three of the four agro-villages analyzed have very low levels of energy security. Only one of the agri-villages showed a satisfactory level of energy security. These findings are consistent with trends observed in other similar studies in the region. The study concluded that measures involving the use of renewable energies, such as solar energy, can increase energy security. This is crucial for guaranteeing sustainable irrigated agriculture and, as a result, food security, ultimately contributing to improving the family income of socially, economically, and environmentally vulnerable populations.